The role of emotional service in the restaurant business - N. A. Ofitserova (Вестник университета)
The article considers the restaurant business from the point of view of not only the entrepreneurial aspect, but also the service aspect, which is fundamental. The reasons why people visit restaurants have been revealed. In addition to physical need, restaurants are an element of cognition and a way of experiencing positive emotions. The importance of the restaurant business in shaping people’s positive emotional state has been formulated. Two forms of emotional labor of an employee and the influence of emotional states on work performance have been highlighted. The role of emotional intelligence and communicative competence in customer satisfaction with a restaurant visit has been determined. The importance of developing emotional intelligence has been concluded. Recommendations for its development has been formulated.